The testicular soma of Tsc22d3 knockout mice supports spermatogenesis and germline transmission from spermatogonial stem cell lines upon transplantation. Issue 6 (19th April 2019) - Zhou, Hai; Zeng, Zhen; Koentgen, Frank; Khan, Mona; Mombaerts, Peter
Abstract: Spermatogonial stem cells (SSCs) are adult stem cells that are slowly cycling and self‐renewing. The pool of SSCs generates very large numbers of male gametes throughout the life of the individual. SSCs can be cultured in vitro for long periods of time, and established SSC lines can be manipulated genetically. Upon transplantation into the testes of infertile mice, long‐term cultured mouse SSCs can differentiate into fertile spermatozoa, which can give rise to live offspring. Here, we show that the testicular soma of mice with a conditional knockout (conKO) in the X‐linked gene Tsc22d3 supports spermatogenesis and germline transmission from cultured mouse SSCs upon transplantation. Infertile males were produced by crossing homozygous Tsc22d3 floxed females with homozygous ROSA26‐Cre males. We obtained 96 live offspring from six long‐term cultured SSC lines with the aid of intracytoplasmic sperm injection. We advocate the further optimization of Tsc22d3‐conKO males as recipients for testis transplantation of SSC lines.